Volume 3: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30194
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Coefficient and Film-Cooling Effectiveness on a Gas Turbine Blade Tip

Abstract: The detailed distributions of heat transfer coefficient and film cooling effectiveness on a gas turbine blade tip were measured using a hue detection based transient liquid crystal technique. Tests were performed on a five-bladed linear cascade with blow down facility. The blade was a 2-dimensional model of a first stage gas turbine rotor blade with a profile of the GE-E3 aircraft gas turbine engine rotor blade. The Reynolds number based on cascade exit velocity and axial chord length was 1.1 × 106 and the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In a review paper on tip heat transfer, Bunker 66 states that for a blade tip there has been very little film-cooling research reported in the literature even though film cooling is widely used. Blowing from the tip has been considered by Kim and Metzger, 67 Kim et al, 68 Kwak and Han, 69,70 Ahn et al, 71 Christophel et al, 72 Acharya et al, 73 and Hohlfeld et al 74 Kim et al 68 present a summary of the experimental work that Metzger performed on tip blowing, as shown in Fig. 22.…”
Section: B Turbine Blade Tipsmentioning
confidence: 99%
“…In a review paper on tip heat transfer, Bunker 66 states that for a blade tip there has been very little film-cooling research reported in the literature even though film cooling is widely used. Blowing from the tip has been considered by Kim and Metzger, 67 Kim et al, 68 Kwak and Han, 69,70 Ahn et al, 71 Christophel et al, 72 Acharya et al, 73 and Hohlfeld et al 74 Kim et al 68 present a summary of the experimental work that Metzger performed on tip blowing, as shown in Fig. 22.…”
Section: B Turbine Blade Tipsmentioning
confidence: 99%
“…Ahn et al 139 presented film-cooling effectiveness results using the PSP technique on a plane and squealer blade tip with one row of holes on the camber line and another row of angled holes near the pressure-side tip. They used the same high flow cascade as the previous study by Kwak and Han 136,137 and investigated the effects of tip-gap clearance (1.0, 1.5, and 2.5 blade span) and blowing ratio (M = 0.5, 1, and 2). Air and nitrogen gas were used as the film-cooling gases, and the oxygen concentration distribution for each case was measured.…”
Section: Turbine Blade Tip Film Cooling Using Pressure Sensitive Painmentioning
confidence: 99%
“…As mentioned by these authors, heat transfer coefficients increase with tip clearance and turbulence intensity. Furthermore, Kwak et al investigated heat transfer on several different squealer geometries. They found that the suction side squealer tips gave the lowest heat transfer coefficient among all the tip geometries tested.…”
Section: Fundamentals Of Heat Transfer In Gas Turbinesmentioning
confidence: 99%